Results of a study on the stress-strain behavior of the cornea in polarized light under conditions of visual work (Ukrainian Journal of Ophthalmology, 2025)
Background: Near visual work causes redistribution of internal stresses in the cornea, leading to a change in the shape and parameters of the interference patterns observed on the cornea in polarized light.Purpose: To assess the effect of various types of visual load on the extraocular muscles (EOM) in children and adolescents on the basis of characteristics of the interference patterns observed on the cornea in polarized light.Material and Methods: The interference patterns observed on the cornea in polarized light were studied in children and adolescents before and after they performed a visual load task which consisted in either working with texts printed on paper at different parameters of convenience for reading (97 individuals) or playing Tetris on a smartphone (58 adolescents). A symmetry coefficient K was calculated for the quantitative assessment of changes in interference pattern parameters induced by visual load.Results: Performing a visual load task which consisted in working with texts printed on paper resulted in a significant increase in asymmetry between the actions of the EOM in 60% to 73% of children; this was indicated by the values of a symmetry coefficient K which were twofold to six-fold higher than normal. Performing a visual load task which consisted in playing Tetris on a smartphone resulted in an increase in asymmetry between the actions of the EOM in 64% of adolescents.Conclusion: Our research confirmed that studies on the stress-strain behavior of the cornea in polarized light are promising for assessing the effect of various types of visual load on the function of EOM.
Keywords: extraocular muscles; polarized light; stress-strain behavior of the cornea; interference patterns; symmetry coefficient